HUBUNGAN DUKUNGAN SUAMI DAN TINGKAT PENDIDIKAN IBU TERHADAP KEBERHASILAN PEMBERIAN ASI EKSLUSIF DI WILAYAH KERJA PUSKESMAS TEGALREJO KOTA YOGYAKARTA - Umihan Samal; Luluk Rosida; Belian Anugrah Estri (Journal of Innovation Research and Knowledge, 2025)
Background: According to the Health Office of the Special Region of Yogyakarta (DIY), the coverage rate of exclusive breastfeeding from 2019 to 2021 did not consistently increase. In 2021, the coverage declined to 80.18% (DIY, 2022). Objective: This study aims to examine the correlation between husband's support and mother's educational level with the success of exclusive breastfeeding in the working area of Tegalrejo Primary Health Center, Yogyakarta. Method: This research employed a quantitative approach with a cross-sectional method. The study population consisted of 228 infants aged 6–12 months, and the sample was selected using a quota sampling technique, resulting in a total of 69 respondents. Data collection was conducted using a questionnaire, which was then compiled into a master table as a reference for data analysis. Results: show that among mothers who received strong support from their husbands, 44 (73.0%) successfully provided exclusive breastfeeding, while only 9 mothers with lower support succeeded. Additionally, 31 mothers (83.3%) with higher education successfully provided exclusive breastfeeding, whereas only 3 mothers with lower education failed. The chi-square statistical test revealed a p-value of 0.000 (p < 0.05), indicating a significant correlation between husband's support and mother's educational level with the success of exclusive breastfeeding in the working area of Tegalrejo Primary Health Center, Yogyakarta. It is recommended that mothers continue breastfeeding until their child reaches the age of two and consistently enhance their knowledge, as scientific advancements continue to evolve. Husbands should optimize their role in providing full support to breastfeeding mothers. Additionally, the primary health center is encouraged to implement mother-supporting group programs, including prenatal exercise and educational sessions on exclusive breastfeeding success for first-trimester mothers or newly married couples at posyandu (integrated health service posts), to further improve exclusive breastfeeding success rates